Twenty years of democracy: An analysis of parliamentary oversight of the military in South Africa since 1994 - Janse van Rensburg, Wilhelm Keyter (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhD)--Stellenbosch University, 2019.